2015
DOI: 10.1021/jacs.5b04843
|View full text |Cite
|
Sign up to set email alerts
|

Successive Stages of Amyloid-β Self-Assembly Characterized by Solid-State Nuclear Magnetic Resonance with Dynamic Nuclear Polarization

Abstract: Self-assembly of amyloid-β (Aβ) peptides in human brain tissue leads to neurodegeneration in Alzheimer's disease (AD). Amyloid fibrils, whose structures have been extensively characterized by solid state nuclear magnetic resonance (ssNMR) and other methods, are the thermodynamic end point of Aβ self-assembly. Oligomeric and protofibrillar assemblies, whose structures are less well understood, are also observed as intermediates in the assembly process in vitro and have been implicated as important neurotoxic sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
126
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(139 citation statements)
references
References 106 publications
9
126
0
Order By: Relevance
“…The intrinsic spin-lattice relaxation rate (i.e., in the absence of paramagnetic doping) is affected by the aggregation state of the solute and its content of methyl groups [11], and can be easily be 0.2 s −1 or greater below 30 K [21]. It should also be noted that, under MAS at low temperatures, ε typically overestimates the enhancement of nuclear spin polarizations relative to their true thermal equilibrium values, largely due to MAS-induced depolarization in the absence of microwave irradiation [30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The intrinsic spin-lattice relaxation rate (i.e., in the absence of paramagnetic doping) is affected by the aggregation state of the solute and its content of methyl groups [11], and can be easily be 0.2 s −1 or greater below 30 K [21]. It should also be noted that, under MAS at low temperatures, ε typically overestimates the enhancement of nuclear spin polarizations relative to their true thermal equilibrium values, largely due to MAS-induced depolarization in the absence of microwave irradiation [30].…”
Section: Discussionmentioning
confidence: 99%
“…The recent surge in DNP-related activity in the solid state NMR community was originally driven by results from the Griffin group, including their demonstration of large NMR signal enhancements at high fields in paramagnetically doped frozen solutions using gyrotron microwave sources [6, 7], their demonstration of efficient DNP at high fields via the cross-effect mechanism [8, 9], and their introduction of nitroxide-based biradical dopants [10]. Applications of DNP in studies of biological [1117] and non-biological [1820] systems are now being actively pursued in many laboratories.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that DNP can drastically increase the sensitivity in solid-state NMR (ssNMR) experiments (Ni et al 2013;Sauvee et al 2013;Song et al 2006) and it has been successfully applied to several biological systems (Becker-Baldus et al 2015;Debelouchina et al 2013;Fricke et al 2015;Gupta et al 2016;Kaplan et al 2015;Koers et al 2014;Potapov et al 2015). Unfortunately, those experiments need to be carried out at cryogenic temperatures as the enhancement factor decreases with increasing temperature (Rosay et al 2010;Sauvee et al 2013;Zagdoun et al 2013).…”
Section: Contentmentioning
confidence: 99%
“…with the co-existence of both on-pathway and off-pathway intermediates. It might be possible to distinguish these intermediate species using novel high-resolution techniques such as dynamicnuclear-polarization-based solid-state NMR spectroscopy (24). However, the presence of multiple pathways will further increase complexity and make high-resolution studies infeasible.…”
mentioning
confidence: 99%